Urban and rural settlements - Carter, Harold (London ; New York : Longman, 1990)
Examines the patterns and functions of human settlements and their g rowth into towns and cities.
Includes index.
Bibliography: p. 183-187.
Keywords: Human settlements; Cities and towns; Villages; Human settlements; Cities and towns